Studies Analysis Management Wastewater Treatment Plant Rinjani South Housing Complex Cirebon City - Roesdiana, Tira; Ases , Fikky Sabillah; Khaerifo , Rifqi (International Journal Labs, 2025)
Wastewater refers to water generated from human or business activities and is categorized into domestic and non-domestic wastewater. Domestic wastewater originates from residential or business activities and is often discharged directly into water bodies without proper treatment, even if it does not meet established quality standards. Wastewater quality standards define acceptable pollutant levels before discharge into water or soil media. Untreated wastewater can pollute the environment, causing water discoloration, foul odors, fish mortality, and the spread of disease. This study examines the centralized domestic wastewater treatment system at the National Housing City (Perumnas) in Cirebon. The research focuses on analyzing the treatment process, evaluating system efficiency, and comparing results to applicable standards and regulations. Data for this thesis were obtained from the Perumnas Wastewater Treatment Plant (IPAL) of Cirebon City, including both primary and secondary data. The main issues studied involve pump capacity and available land for plant expansion. The Perumnas IPAL is designed to treat domestic wastewater with a capacity of 6,000 SL. Assuming one SL serves four people and daily water consumption is 180 L/person/day, the estimated wastewater flow is 3,456 m³/day. The wastewater is processed in three types of ponds: an anaerobic pond (1 unit), a facultative pond (1 unit), and two maturation ponds, with the treated output intended for PDAM water use.